The burning earth: An environmental history of the last 500 years - Amrith, Sunil (UK Allen Lane, 2024)
In this paradigm-shifting global history of how humanity has reshaped the planet, and the planet has shaped human history, Sunil Amrith twins the stories of environment and Empire, of genocide and eco-cide, of the expansion of human freedom and its costs. Drawing on an extraordinarily rich diversity of primary sources, he reckons with the ruins of Portuguese silver mining in Peru, British gold mining in South Africa, and oil extraction in Central Asia. He explores the railways and highways that brought humans to new terrains of battle against each other and against nature. Amrith$1 (Bs account of the ways in which the First and Second World Wars involved the massive mobilization not only of men, but of other natural resources from around the globe, provides an essential new way of understanding war as an irreversible reshaping of the planet. He also reveals the reality of migration as consequence of environmental harm.s
Keywords: Human Geography; Natural resources-History; World-History